2020
DOI: 10.3389/fmicb.2020.01516
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Assay to Assess Salmonella enterica Persistence in Lettuce Leaves After Low Inoculation Dose

Abstract: Salmonella enterica is an enterobacterium associated with numerous foodborne illnesses worldwide. Leafy greens have been a common vehicle for disease outbreaks caused by S. enterica. This human pathogen can be introduced into crop fields and potentially contaminate fresh produce. Several studies have shown that S. enterica can survive for long periods in the plant tissues. Often, S. enterica population does not reach high titers in leaves; however, it is still relevant for food safety due to the low infective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Taking advantage of the lettuce genotypic variability, we used two contrasting lettuce cultivars, Red Tide (RT) and Lollo Rossa (LR) and observed that the S. enterica isolates used in this study overall tend to survive better on RT than LR, individually ( Figure 1 ) or combined in pools ( Supplementary Figure S2 ). This finding is in agreement with the previously described increased fitness of E. coli O157:H7 and S. enterica serovar Typhimurium 14028s on RT ( Jacob and Melotto, 2020 ; Oblessuc and Melotto, 2020 ). It is possible that these bacterial pathogens of humans interact with the plant as commensals, occupying the phyllosphere while not benefiting or harming the host.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Taking advantage of the lettuce genotypic variability, we used two contrasting lettuce cultivars, Red Tide (RT) and Lollo Rossa (LR) and observed that the S. enterica isolates used in this study overall tend to survive better on RT than LR, individually ( Figure 1 ) or combined in pools ( Supplementary Figure S2 ). This finding is in agreement with the previously described increased fitness of E. coli O157:H7 and S. enterica serovar Typhimurium 14028s on RT ( Jacob and Melotto, 2020 ; Oblessuc and Melotto, 2020 ). It is possible that these bacterial pathogens of humans interact with the plant as commensals, occupying the phyllosphere while not benefiting or harming the host.…”
Section: Discussionsupporting
confidence: 93%
“…LSLB medium was supplemented with either 15 μg/mL tetracycline or 60 μg/mL kanamycin, as appropriate. Upon reaching an OD 600 of 0.7 to 0.9, bacterial cells were collected by centrifugation and a two-step dilution process was used to prepare the inoculum as described by Oblessuc and Melotto (2020) for a final concentration of 1 x 10 3 CFU/mL. To make inocula with pools of multiple S. enterica isolates ( Table 2 ), equal amounts of each isolate were added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation